The impact of a nutrition and health programme on the socio-economic status and food access of households in Suba District, Kenya - King´olla, B; Ohiokpehai, O; Mbithe David, D (2009)
Objective: Poor nutrition and ill health affect the productivity, livelihoods and food access of a household. This study investigated the impact of a nutrition and health programme on the socioeconomic status and food access of households in Suba district, Kenya. Methodology and results: Action research design was utilized that involved comparison of the baseline and impact evaluation results after a three-year intervention period. A sample size of 291 randomly selected households from a community whose main economic activity is fishing was used. Data collection instruments included a structured questionnaire, focus group discussion guide and an observation checklist. Data was analyzed using SPSS computer package version 16. A P-value of <0.05 was considered significant. Over a three-year period, household size increased from 4.8 to 5.5. Education levels improved insignificantly (P>0.05) while income levels improved with monthly maternal income improving from a minimum of Ksh. 100 to 300 (1.5 to 4.0 US dollars). About 89.6 and 3.4% of households obtained food from own produce and purchase combined with assistance, respectively. About 51.2, 3 and 64% reported to consider their households food secure when there was clear moonlight as the fishermen in their households were assured of a good fish catch, at the end of the month when households had some cash income, and if they harvested between 2 to 5 bags of maize (each 90kg), per season, respectively. More than a third (32.6%) of the respondents were involved in small business while 50.9 and 16.5% were involved in actual fishing and farming, respectively. Only 6.2% of the respondents had access to credit facilities. After 3 years, food consumption patterns did not change significantly from the baseline. Sanitation and morbidity patterns did not improve significantly at the households albeit with nutrition and health education, with 27.5 and 30.9% not having latrines and refuse disposal bins/pits, respectively. The households bathed, washed and drew drinking water from the same point in Lake Victoria. Conclusion and potential application of findings: Nutrition and health programmes have potential to improve the socioeconomic status and household food access depending on content coverage of the programmes.